2017
DOI: 10.3390/molecules22111822
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Triazolonaphthalimide Derivative LSS-11 Synergizes the Anti-Proliferative Effect of Paclitaxel via STAT3-Dependent MDR1 and MRP1 Downregulation in Chemoresistant Lung Cancer Cells

Abstract: Multidrug resistance (MDR) is a major cause of the inefficacy and poor response to paclitaxel-based chemotherapy. The combination of conventional cytotoxic drugs has been a plausible strategy for overcoming paclitaxel resistance. Herein, we investigated the cytotoxic effects and underlying mechanism of LSS-11, a novel naphthalimide derivative-based topoisomerase inhibitor, in paclitaxel-resistant A549 (A549/T) lung cancer cells. LSS-11 enhanced cell death in A549/T cells by inducing apoptosis through increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…The same applies for rofecoxib (Figure ), which showed to downregulate mRNA and protein levels of MRP1, but also GST, at a concentration of 10 μM using BGC‐823 gastric cancer cells . Here, it is worth to mention that downregulation of MRP1 transcript and protein has also been observed for other pharmacological and experimental drugs, such as fidarestat, LSS‐11, pantoprazole, and U0126 (Figure ) …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 55%
“…The same applies for rofecoxib (Figure ), which showed to downregulate mRNA and protein levels of MRP1, but also GST, at a concentration of 10 μM using BGC‐823 gastric cancer cells . Here, it is worth to mention that downregulation of MRP1 transcript and protein has also been observed for other pharmacological and experimental drugs, such as fidarestat, LSS‐11, pantoprazole, and U0126 (Figure ) …”
Section: Pharmacological and Experimental Drugs And Synthetic Analogssupporting
confidence: 55%
“…Regarding the interplay between STAT3, its target genes and MDR1, Ji et al 32 showed that a novel triazolonaphthalimide derivative LSS-11 could hinder the binding of STAT3 to the MDR1 and MRP1 promoters by conducting chromatin coimmunoprecipitation (ChIP) assay. Indicating MDR1 is regulated by the STAT3 at the transcription level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA LINC00460 promotes EGFR expression by downregulating miR-769-5p, which results in the resistance of NSCLC cells to gefitinib ( 220 ). LncRNA MALAT1 upregulates multiple drug resistance-related protein (MDR1) and multidrug resistance protein (MDR1) by inducing STAT3 phosphorylation, which eventually enhance the resistance of lung cancer cells to treatment with cisplatin ( 221 , 222 ). Though there is no specific clinical trial targeting lung cancer, it’s still a potential therapy for the comprehensive treatment of lung cancer.…”
Section: Current and Next Generation Therapiesmentioning
confidence: 99%